Recycling method of ceramic fiber catalyst tube
By purge, ultrasonic cleaning, vacuum impregnation and drying of the used ceramic fiber catalyst tube, the problem of inability to recover the catalyst catalyst is solved, and secondary utilization and effective utilization of resources are achieved.
Patent Information
- Application Number
- CN202510063957.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-15
AI Technical Summary
After the ceramic fiber catalyst tube is used, the catalyst catalyst cannot be effectively recycled, resulting in waste of resources and environmental pollution. The service life of the catalyst tube is short and needs to be replaced frequently.
Through steps such as purge, ultrasonic cleaning, vacuum impregnation and drying of polysilazane solution, the used ceramic fiber catalyst tube is processed to restore its catalytic activity and achieve secondary utilization.
Effective recycling and secondary utilization of ceramic fiber catalyst tubes after use is achieved, extending their service life, reducing resource consumption and environmental pollution.
Smart Images

Figure CN119819382A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for recovering a ceramic fiber catalyst tube, belonging to the technical field of ceramic fiber catalyst tubes. Background Art
[0002] With the rapid development of metallurgy, chemical industry, building materials and other industries, the amount of dust, nitrogen oxides, sulfur dioxide and other gases discharged into the atmosphere each year is increasing, causing many problems such as air pollution and greenhouse effect. Therefore, the purification of these waste gases has become the key to alleviating environmental crises. Ceramic fiber filter tubes are made of ceramic fiber, silica sol and other raw materials, which are stirred to obtain a uniform slurry, then formed by vacuum filtration, and then dried and calcined. The surface of the ceramic fiber filter tube is impregnated with a catalyst solution, and then dried to obtain a ceramic fiber filter tube with a catalyst.
[0003] The use process is as follows: first, calcium hydroxide powder is sprayed into the high-temperature flue gas to make the sulfur dioxide in the flue gas react with calcium hydroxide to achieve the purpose of removing sulfur dioxide; ammonia water is sprayed into the flue gas, and the flue gas with ammonia water continues to pass through the ceramic fiber catalyst tube, and the dust particles are deposited on the surface of the filter tube, and the dust on the surface of the filter tube is blown off into the dust collector through the pulse backblowing process; the purified flue gas is converted into N2 by the catalyst on the surface of the ceramic fiber catalyst tube, thereby achieving the purpose of desulfurization, denitrification and dust removal, so as to emit gases that meet the emission requirements.
[0004] During the use of ceramic fiber catalyst tubes, fine particles in the smoke will pass through the surface of the catalyst tube and enter the interior of the catalyst tube. Pulse backflushing cannot remove these particles from the interior of the catalyst tube, which will reduce the air permeability of the catalyst tube and affect its performance. Low-melting-point Na2O and K2O alkaline particles in the dust enter the interior of the catalyst tube and react with the catalyst, causing the catalyst to be alkaline poisoned and reduce its activity. After long-term use, the catalyst will lose its catalytic activity and lose its catalytic performance for decomposing NxO pollutants. Therefore, in the actual use of ceramic fiber catalyst tubes, the service life of the catalyst tube will be determined according to the emission of flue gas. The service life of the catalyst tube is generally 5-6 years. The used catalyst tube is regarded as ceramic fiber solid waste, and the heavy metals in the catalyst will pollute the land and water sources if not handled properly. Therefore, the recycling of the used catalyst tube is an urgent problem that needs to be solved. Summary of the invention
[0005] In view of this, the present invention provides a method for recycling ceramic fiber catalyst tubes. The technical problem to be solved is how to improve a method for recycling ceramic fiber catalyst tubes so that the used catalyst tubes can be processed to achieve the purpose of secondary utilization.
[0006] The purpose of the present invention and the solution to the technical problem are achieved by adopting the following technical measures. A method for recycling ceramic fiber catalyst tubes proposed by the present invention comprises the following steps:
[0007] Step 1, purging the inside and outside of the catalyst tube;
[0008] Step 2, ultrasonically cleaning the purged catalyst tube, then taking out the catalyst tube and drying it;
[0009] Step 3, vacuum impregnating the dried catalyst tube with a polysilazane solution, drying at low temperature, and heating to cure;
[0010] Step 4: spray the catalyst solution into the interior of the ceramic fiber filter tube, dry it, and calcine it to obtain a ceramic fiber catalyst tube that can be reused.
[0011] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.
[0012] Preferably, in the aforementioned method for recycling ceramic fiber catalyst tubes, in step 1, the purging pressure is 0.1 MPa-0.2 MPa.
[0013] Preferably, in the aforementioned method for recycling ceramic fiber catalyst tubes, in step 2, the catalyst tube is placed flat in water, the water completely submerges the catalyst tube and is 5 cm to 8 cm higher, and then the catalyst tube is ultrasonically cleaned.
[0014] Preferably, in the aforementioned method for recycling ceramic fiber catalyst tubes, in step 2, the frequency of the ultrasonic wave is 20kHZ-40kHZ.
[0015] Preferably, in the aforementioned method for recycling ceramic fiber catalyst tubes, in step 2, the drying temperature is 110° C.-130° C., and the drying time is 10 h-12 h.
[0016] Preferably, in the aforementioned method for recycling ceramic fiber catalyst tubes, in step three, the concentration of the polysilazane solution is 5wt%-15wt%.
[0017] Preferably, in the aforementioned method for recycling ceramic fiber catalyst tubes, in step three, the vacuum degree of the vacuum impregnation is lower than 1000Pa.
[0018] Preferably, in the aforementioned method for recycling ceramic fiber catalyst tubes, in step three, the temperature of the low-temperature drying is 50° C.-60° C., and the time is 3 h-5 h.
[0019] Preferably, in the aforementioned method for recycling ceramic fiber catalyst tubes, in step three, the curing temperature is 160° C.-200° C., and the curing time is 1 h-3 h.
[0020] Preferably, in the aforementioned method for recycling ceramic fiber catalyst tubes, in step 4, the catalyst solution is a 3wt%-8wt% V2O5-WO3 / TiO2 catalyst solution.
[0021] Preferably, in the aforementioned method for recycling ceramic fiber catalyst tubes, in step 4, the drying temperature is 105° C.-120° C., and the drying time is 10 h-15 h.
[0022] Preferably, in the aforementioned method for recycling ceramic fiber catalyst tubes, in step 4, the calcination temperature is 300° C.-350° C., and the calcination time is 5 h-8 h.
[0023] Compared with the prior art, the recycling method of the ceramic fiber catalyst tube of the present invention has the following advantages:
[0024] Beneficial effects:
[0025] The ceramic fiber catalyst tube recycling method of the present invention can process the used catalyst tube to achieve the purpose of secondary utilization;
[0026] The method for recycling ceramic fiber catalyst tubes of the present invention solves the problem that the catalyst in the used catalyst tubes cannot be recycled;
[0027] The ceramic fiber catalyst tube recycling method of the present invention reduces the filtration molding process of ceramic fibers, reduces the use of raw materials such as aluminum silicate fibers and silica sol, and is energy-saving and environmentally friendly.
[0028] The volume density of the reusable ceramic fiber catalyst tube obtained by the present invention is 0.53g / cm 3 -0.54g / cm 3 The porosity is 68.2%-69.8%, the filtration pressure drop is 850Pa-910Pa, and the denitrification efficiency is 92%-98%.
[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram of the fiber surface composition of the recycled ceramic fiber tube in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation method, structure, characteristics and effects of a ceramic fiber catalyst tube recovery method proposed by the present invention are described in detail below in combination with the preferred embodiment. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0032] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the usual meanings understood by ordinary technicians in the field to which the present invention belongs. If no specific experimental steps or conditions are specified below, the operations or conditions of the conventional experimental steps described in the literature in the field can be followed.
[0033] Some embodiments of the present invention provide a method for recycling a ceramic fiber catalyst tube, comprising the following steps:
[0034] S1 uses a compressed air spray gun to purge the inside and outside of the catalyst tube. The pressure range of the compressed air is 0.1MPa-0.2MPa. Within this pressure range, the spray gun can remove the dust particles remaining in the catalyst tube. If it is less than 0.1MPa, the compressed air pressure is too small, and the dust particles inside the catalyst tube cannot be removed well; if it is greater than 0.2MPa, the compressed air pressure is too high, which will destroy the fiber structure on the surface of the catalyst tube and endanger the health of the operator.
[0035] S2 places the catalyst tube flat in an ultrasonic tank filled with water, supports the bottom with a support, and the water completely submerges the catalyst tube and is 5cm-8cm higher. If it is less than 5cm, there is too little water to completely submerge the catalyst tube. During ultrasonic treatment, the ultrasonic wave cannot act on the catalyst tube through the water. If it is greater than 8cm, there is too much water, which causes inconvenience in taking and placing the catalyst tube. Turn on the ultrasonic controller, the frequency range of the ultrasonic wave is between 20kHZ-40kHZ. The low-frequency ultrasonic wave has stronger penetrating power and can better enter the interior of the catalyst tube. Continue to clean the particles in the gaps of the catalyst tube with an ultrasonic method; the catalyst on the surface of the ceramic fiber will also partially fall off and enter the water under the condition of ultrasound.
[0036] S3 takes the catalyst tube out of the ultrasonic water tank, places it on a drying support frame, and transfers the drying support frame to an oven for drying. The drying temperature is between 110°C and 130°C, and the drying time is between 10h and 12h. This drying system can completely dry the catalyst tube.
[0037] S4 uses butyl acetate as solvent, prepares the polysilazane solution of concentration 5wt%-15wt%, and adds the polysilazane solution into the vacuum impregnation container. If the concentration of polysilazane solution is less than 5wt%, polysilazane cannot completely cover the surface of ceramic fiber in catalyst tube after impregnation; If the concentration of polysilazane solution is higher than 15wt%, the viscosity of polysilazane solution increases, which is not conducive to subsequent impregnation process. The catalyst tube after step S3 drying is put into vacuum impregnation container for impregnation, and vacuumization makes the vacuum degree in the container lower than 1000Pa. In the process of vacuuming, polysilazane solution adheres to the surface of ceramic fiber inside catalyst tube, and the impregnation time is 10min-30min, after which catalyst tube is taken out from vacuum impregnation container, put into 50 ℃-60 ℃ oven and dry for 3h-5h, so that butyl acetate solvent volatilization is completely volatilized, and polysilazane adheres to the surface of ceramic fiber. Then the temperature is raised to 160-200°C and dried for 1-3 hours to solidify the polysilazane. The polysilazane solidified at this temperature forms a stable organic film on the surface of the ceramic fiber. If the temperature is lower than 160°C or the time is less than 1 hour, the polysilazane cannot be solidified during the drying process; if the temperature is higher than 200°C or the time is greater than 3 hours, the polysilazane will undergo a ceramic reaction, causing the volume of the polysilazane coating to shrink.
[0038] S5 selects a V2O5-WO3 / TiO2 system catalyst, uses water as a solvent, and prepares a V2O5-WO3 / TiO2 catalyst solution with a solid content of 3wt%-8wt%. If the solid content of the catalyst is too low, the NO and NO2 in the flue gas cannot be completely converted into N2 during use in the ceramic fiber tube, resulting in poor denitration effect; if the solid content of the catalyst is too high, the pores in the ceramic fiber tube are blocked, the porosity of the ceramic fiber tube is reduced, the pressure drop value during use is increased, and the energy consumption is increased.
[0039] The catalyst is fixed on the rotating device, and the switch is turned on to rotate the catalyst tube, and the rotation speed is 20 rpm-60 rpm; the spraying device is extended into the interior of the catalyst tube, and the spraying switch is turned on. The catalyst slurry is sprayed into the interior of the catalyst tube through the spraying device, and the spraying time is 10min-15min; the rotating catalyst tube is conducive to the uniform penetration of the catalyst slurry into the interior of the catalyst tube, so that the catalyst is evenly present in the catalyst tube.
[0040] Take the catalyst tube out of the rotating device, put it into a constant temperature drying oven, and dry it at 105℃-120℃ for 10h-15h. If it is lower than 105℃, the temperature is too low, and the catalyst solvent evaporates slowly, which will prolong the drying time and reduce production efficiency; if it is higher than 120℃, the temperature is too high, which will cause inconvenience to the workers.
[0041] Then transfer to a high temperature furnace and heat to 300°C at a heating rate of 2°C / min-5°C / min.
[0042] After calcining at -350℃ for 5h-8h and cooling, a ceramic fiber catalyst tube with a catalyst loading rate of about 3.0wt%-8.0wt% is obtained. The calculation method of the catalyst loading rate in the ceramic fiber catalyst tube is:
[0043] Catalyst loading rate = (W1-W0) / W0×100%
[0044] Where: W0 is the mass of the ceramic fiber tube after drying at 105℃-120℃ for 10h-15h, kg;
[0045] W1 is the mass of the ceramic fiber catalyst tube after calcination at 300℃-350℃ for 5h-8h, kg;
[0046] The present invention is further described below in conjunction with specific embodiments.
[0047] Example 1
[0048] Select a used ceramic fiber catalyst tube and use 0.1MPa dry compressed air to purge its inner and outer surfaces to purge the smoke particles attached to the surface. Place the ceramic fiber catalyst tube in an ultrasonic tank with the water surface 5cm higher than the upper surface of the catalyst tube. Turn on the ultrasonic generator with an ultrasonic frequency of 20kHZ. Use ultrasonic energy vibration to separate the smoke particles and catalyst inside the catalyst tube from the ceramic fiber. Collect the separated smoke particles and catalyst to prevent the catalyst from polluting the water and soil. Place the ultrasonically treated catalyst tube in a blast high-temperature oven at 110°C and dry it for 10 hours to completely dry the catalyst tube.
[0049] Using a differential pressure gauge, the pressure difference of the drying catalyst tube is detected under the condition of a gas flow rate of 1m / min; if the pressure difference is greater than 1000Pa, it means that the porosity of the ceramic fiber catalyst tube does not meet the requirements for reprocessing.
[0050] With butyl acetate as solvent, a polysilazane solution with a solid content of 5wt% is prepared and mechanically stirred into a uniform solution. The dried catalyst tube is placed in the polysilazane solution for immersion, and the vacuum degree in the container is evacuated to 900Pa, and the immersion time is 10min. Blast drying at 60℃ for 5h to evaporate the butyl acetate solvent, and the polysilazane adheres to the surface of the ceramic fiber as a coating. The temperature is then raised to 180℃ and dried for 2h to solidify the polysilazane. The polysilazane solidified at this temperature forms a stable organic film on the surface of the ceramic fiber.
[0051] Take TiO2 with a particle size of 100nm as the carrier, ammonium metatungstate as the precursor of WO3, the mass ratio of WO3 / TiO2 is 5:95, and water is used as the solvent to prepare a slurry with a mass fraction of 10%. Mechanical ultrasonic stirring for 30 minutes, pour the stirred slurry into an iron plate, put it into a -40℃ freezer, freeze it for 2 hours, so that the water in the slurry changes from liquid to solid ice. Take out the iron plate and the material together, put it on the heating plate of the freeze dryer, set the temperature of the heating plate to 40℃, the vacuum degree to 10Pa, and the drying time to 15 hours. Take out the freeze-dried powder from the iron plate, put it into an alumina ceramic crucible, put the crucible and the material into a 300℃ resistance furnace, and roast it for 5 hours to obtain WO3 / TiO2 powder.
[0052] Ammonium metavanadate was used as the precursor of V2O5, the mass ratio of V2O5 to WO3 / TiO2 was 5:95, water was used as the solvent, and a slurry with a mass fraction of 10% was prepared, and ultrasonic stirring was performed at 20kHZ for 30 minutes. The subsequent treatment process was the same as the preparation of WO3 / TiO2 powder, and finally (V2O5-WO3) / TiO2 catalyst powder was obtained.
[0053] Using water as solvent, the prepared catalyst is formulated into a solution with a mass fraction of 5wt%, the catalyst tube is fixed on a rotating device, the switch is turned on, and the catalyst tube is rotated at a speed of 30 rpm; the spraying device is extended into the interior of the catalyst tube, the spraying switch is turned on, and the catalyst solution is sprayed into the interior of the catalyst tube through the spraying device, and the spraying time is 10 minutes; the rotating catalyst tube is conducive to the catalyst slurry to evenly penetrate into the interior of the catalyst tube, so that the catalyst is evenly present in the catalyst tube.
[0054] The catalyst tube was taken out from the rotating device, placed in a constant temperature drying oven, and dried at 105°C for 10 hours. It was then transferred to a high temperature furnace and heated to 300°C at a heating rate of 2°C / min for calcination for 5 hours and then cooled to obtain a ceramic fiber catalyst tube with a catalyst loading rate of about 8.0wt%. After calcination, the polysilazane was decomposed and cross-linked, and the catalyst and the ceramic fiber were more closely bonded. Its surface state is as follows: Figure 1 As shown. Figure 1 It can be seen that after the impregnation and drying of the polysilazane solution, a layer of polysilazane coating 1 is formed on the surface of the ceramic fiber. After the catalyst is impregnated, the catalyst particles are deposited on the polysilazane coating 1. When the polysilazane coating 1 is heated, the polysilazane coating 1 is decomposed and cross-linked, so that the bonding state between the ceramic fiber 2 and the catalyst 3 changes from physical bonding to chemical bonding.
[0055] Example 2
[0056] The difference between this embodiment and embodiment 1 is that the catalyst of this embodiment is prepared into a solution with a mass fraction of 7 wt%, and the remaining steps and parameters are the same as those of embodiment 1. In this embodiment, a ceramic fiber catalyst tube with a catalyst loading rate of about 9.0 wt% is obtained.
[0057] Example 3
[0058] The difference between this embodiment and embodiment 1 is that the solid content of the polysilazane solution in this embodiment is 10 wt %, and the remaining steps and parameters are the same as those in embodiment 1. In this embodiment, a ceramic fiber catalyst tube with a catalyst loading rate of about 8.4 wt % is obtained.
[0059] Example 4
[0060] The difference between this embodiment and embodiment 1 is that the solid content of the polysilazane solution in this embodiment is 15wt%, and the remaining steps and parameters are the same as those in embodiment 1. In this embodiment, a ceramic fiber catalyst tube with a catalyst loading rate of about 8.8wt% is obtained.
[0061] Example 5
[0062] The difference between this embodiment and embodiment 1 is that the catalyst of this embodiment is prepared into a solution with a mass fraction of 3 wt%, and the remaining steps and parameters are the same as those of embodiment 1. In this embodiment, a ceramic fiber catalyst tube with a catalyst loading rate of about 4.0 wt% is obtained.
[0063] Example 6
[0064] The difference between this embodiment and embodiment 1 is that the ultrasonic cleaning frequency of this embodiment is 40 kHz, and the remaining steps and parameters are the same as those of embodiment 1. The ceramic fiber catalyst tube with a catalyst loading rate of about 4.0 wt% obtained in this embodiment.
[0065] The reusable ceramic fiber catalyst tubes obtained in Examples 1-6 were tested for volume density, porosity, filtration pressure drop and denitrification efficiency. The test results are shown in Table 1.
[0066] Volume density and porosity: Prepare a 5cm×5cm×2cm sample from the ceramic fiber catalyst tube, weigh it and record its weight as m1; put the sample into the immersion tank, and place it in the vacuum device, evacuate it until the residual pressure is less than 2500Pa, inject tap water into the immersion tank until the sample is completely submerged, and continue to evacuate for 30 minutes; use a balance device to measure the suspended weight m2 and saturated weight m3 of the sample after immersion. Use the following formula to calculate the volume density and porosity:
[0067] where ρ ing -Density of tap water at test temperature
[0068]
[0069] Filtration pressure drop: Place the ceramic fiber catalyst tube into a self-made filtration device. The test gas is discharged through the ceramic fiber catalyst tube at a speed of 1.2m / min. The pressure difference between the test inlet chamber and the exhaust chamber is the filtration pressure drop.
[0070] Denitration efficiency: The denitration performance test of the catalyst is carried out on the catalyst denitration activity evaluation platform. It consists of three parts, namely the simulated flue gas part, the catalytic reaction part and the flue gas analysis part. The reaction is provided by four different high-pressure gas cylinders with N2, O2, NH3 and NO required for the reaction. The four gases are mixed into simulated flue gas through the gas manifold and enter the reaction tube to contact the catalyst to be tested to react. The gas flow is controlled by a mass flow meter; the reaction temperature is controlled by an electric heating furnace, and finally the simulated flue gas is measured by a flue gas analyzer to measure the NO concentration before and after the reaction.
[0071]
[0072] C in represents the concentration of inlet NO and C out Represents the outlet NO concentration.
[0073] Table 1
[0074]
[0075]
[0076] From the data in Table 1, it can be seen that the volume density of the reusable ceramic fiber catalyst tube obtained in Examples 1-6 of the present invention is 0.53 g / cm 3 -0.54g / cm 3 The porosity is 68.2%-69.8%, the filtration loss is 850Pa-910Pa, and the denitrification efficiency is 92%-98%.
[0077] The above embodiments are only used to explain the content of the present invention, and are not intended to limit the present invention. Simple technical variations within the technical concept of the present invention should be considered to be covered by the content disclosed by the present invention and belong to the protection scope of the present invention.
[0078] In the specification of the present invention, a lot of specific details are described. However, it is understood that embodiments of the present invention can be practiced without these specific details. In some embodiments, well-known methods, structures and techniques are not shown in detail so as not to obscure the understanding of this specification.
[0079] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0080] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0081] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for recycling ceramic fiber catalyst tubes, characterized in that: The following steps are involved: Step 1, purging the inside and outside of the catalyst tube; Step 2: ultrasonically clean the purged catalyst tube, then take out the catalyst tube and dry it; Step 3, vacuum impregnating the dried catalyst tube with a polysilazane solution, drying at low temperature, and heating to cure; Step 4: spray the catalyst solution into the interior of the ceramic fiber filter tube, dry it, and calcine it to obtain a ceramic fiber catalyst tube that can be reused.
2. The method for recycling ceramic fiber catalyst tubes according to claim 1, characterized in that: In step 1, the purging pressure is 0.1MPa-0.2MPa.
3. The method for recycling ceramic fiber catalyst tubes according to claim 1, characterized in that: In step 2, the catalyst tube is placed flat in water, the water completely submerges the catalyst tube and is 5 cm to 8 cm higher than the catalyst tube, and then the catalyst tube is ultrasonically cleaned.
4. The method for recycling ceramic fiber catalyst tubes according to claim 1, characterized in that: In step 2, the frequency of the ultrasonic wave is 20kHZ-40kHZ.
5. The method for recycling ceramic fiber catalyst tubes according to claim 1, characterized in that: In step 2, the drying temperature is 110° C.-130° C., and the drying time is 10-12 hours.
6. The method for recycling ceramic fiber catalyst tubes according to claim 1, characterized in that: In step 3, the concentration of the polysilazane solution is 5wt%-15wt%.
7. The method for recycling ceramic fiber catalyst tubes according to claim 1, characterized in that: In step three, the vacuum degree of the vacuum impregnation is lower than 1000Pa.
8. The method for recycling ceramic fiber catalyst tubes according to claim 1, characterized in that: In step three, the temperature of low-temperature drying is 50°C-60°C, and the time is 3h-5h.
9. The method for recycling ceramic fiber catalyst tubes according to claim 1, characterized in that: In step three, the curing temperature is 160°C-200°C and the curing time is 1h-3h.
10. The method for recycling ceramic fiber catalyst tubes according to claim 1, characterized in that: In step 4, the catalyst solution is a 3-8wt% V2O5-WO3 / TiO2 catalyst solution; the drying temperature is 105°C-120°C, and the drying time is 10h-15h; the calcination temperature is 300°C-350°C, and the calcination time is 5h-8h.